The Implementation Of Morning Conversation Program On Students’ Speaking Skill Of English Student Community At Pondok Pesantren Al Bidayah Tegal Besar Jember - As’ari, As’ari; Mufidah, Zahratul Maujudatul; Farhan, Saiful (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2023)
The Morning Conversation Program (MCP) was implemented by the English Student Community at Pondok Pesantren Al Bidayah Tegal Besar Kaliwates Jember to improve students' speaking skills. The program, conducted three times a week, aimed to teach vocabulary, flexibility in speaking due to frequent reading, and increase self-confidence among intermediate class students. The research focused on the implementation and impact of the MCP on students' speaking skills. The study used a descriptive research design with a qualitative approach, with interviews, observations, and documentation as research instruments. The results showed that the MCP positively impacted students' speaking skills, including mastering vocabulary, enhancing flexibility in speaking due to frequent reading, and increasing self-confidence.